Association between sleep quality and habits of electronic media use among young adults with different circadian typology - Anil Kumar Gangwar,; Anita Rawat,; Suryakanta Seth,; Ajay Verma,; Suryakant, (Asian Journal of Medical Sciences, 2024)
Background: Circadian preference refers to individual differences for mental and physical activity in the morning and evening. We hypothesized, that inadvertent use of electronic media can cause circadian misalignment that influences sleeping habits and sleep quality of young adults. Aims and Objectives: The aim of the study was to investigate the effect of circadian preferences on sleeping habits and the association of electronic media use with sleep quality and sleep disturbances. Materials and Methods: A total of 188 subjects were enrolled and divided into three groups: Evening, intermediate, and morning chronotype based on the Morningness-Eveningness score. Electronic media use at bedtime and duration of use were assessed subjectively. Sleep quality and subjective sleep disturbances, daytime sleepiness, and chronotype were assessed by the Pittsburgh Sleep Quality Index, Epworth Sleepiness Score, and Morningness-Eveningness Questionnaire Self-assessment version, respectively. Results: The majority of subjects with the evening chronotypes suffered from poor sleep quality compared to other chronotypes and the difference was statistically significant. In evening-type subjects, electronic media use at bedtime, long sleep latency, short sleep duration, and daytime sleepiness were significantly associated with poor sleep quality with odds ratios of 2.34 (1.08–5.08), 11.42 (4.98–26.19), 8.54 (1.01–68.24), and 1.68 (1.03–2.73), respectively. Conclusion: The majority of evening-type subjects had poor sleep quality, altered sleeping habits, and electronic media use at bedtime is significantly associated with poor sleep quality. Hence, history regarding sleep habits and lifestyle, especially electronic media use, should be taken from young adults, who are coming to the outpatient department for other than sleep disorders, to prevent the development of health-related problems.